Fungal- and Algal-Derived Synthesis of Various Nanoparticles and Their Applications - Anugrah Michael; Aniket Singh; Arpita Roy; Md. Rabiul Islam (Bioinorganic Chemistry and Applications)
Nanoparticles synthesis through biological mediated methods with a particular focus on the processes mediated by fungi and algae is discussed, which systematically reviews nanoparticle characterization, composition, synthesis methods, and, lastly but not least, the applications of NPs across five different categories to provide a reference for future research. Most traditional methods to generate nanoparticles have certain limitations, like the toxicity of precursor materials, the need for high-temperature management, and the high cost of synthesis, which ultimately hinders their utility in sectors. Greener synthesis through fungus and algae done through bioreduction by biomolecules or enzymes present in them is low-energy, low-cost, and needs a low-temperature environment, providing a unique technique for the manufacture of various metallic nanoparticles utilized in an array of industries and healthcare.